ANALISIS PENGGUNAAN GAYA BAHASA DALAM ANTOLOGI CERPEN MAWAR HITAM KARYA CANDRA MALIK - Jaenudin Jaenudin; Nanang Kosim; Raden Mekar Ismayani (IKIP Siliwangi, 2018)
This research aims to analyze the locution which is contained in the book short stories anthology entitled Mawar Hitam by Candra Malik. The method in this research is the descriptive method by using structural approach. The sources of the data in this research are 5 short stories from overall short story which amounted 20. The data in this research are quotations obtained from the analysis that show the use of locution. The locution that focuses on this research are repetition, assonance, hyperbola, paradox, personification, and periphrasis. Based on data analysis, it can be concluded: (1) locution of repetition cover 5, assonance cover 10, hyperbola cover 4, paradox cover 2, personification cover 5 and periphrasis cover 6. Amounted of 32 uses of locution on five short stories that have been analyzed; (2) the short story with using the most locution is the short story entitled Membaca Tubuhmu, with using 12 of locution. The short story with the least use of locution is the short story entitled Selimut Nona Clara, with using 4 locutions.